Use of a success-oriented GO-FLOW method for system configuration risk management at NPPs. (August 2020) - Yang, Jun; Wang, Ming; Guo, Dingqing; Zhang, Bing; Yang, Ming
Highlights: A framework of integrated risk monitor system is presented. The GO-FLOW method is used to develop the integrated risk monitor system. Case study of safety injection system under MBLOCA is conducted for plant configuration risk management. Global risk insights could be attained by the integrated risk monitor system. Abstract: In this paper, a framework of improved risk monitor system that integrates multiple applications of retrospective investigation analysis of risk factors, point-in-time risk monitoring and proactive risk management is presented. Among these applications capabilities, the plant configuration risk management is implemented and demonstrated with a safety injection system in the event of medium-break LOCA at nuclear power plants. The system reliability and safety analysis are conducted on the success-oriented logic models using GO-FLOW method. Both quantitative and qualitative risk measures addressed respectively by risk matrix and goal tree-success tree scheme with risk band display could provide global risk insights regarding plant configuration control.